2015
DOI: 10.1039/c5ra20233g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative performance of online SPE-LC coupled to Q-Exactive for the analysis of sofosbuvir in human plasma

Abstract: A quantitative strategy towards the detection of sofosbuvir in human plasma was developed with online-SPE-LC-HRMS using t-MS2, t-SIM and F-SIM modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(34 reference statements)
0
13
1
Order By: Relevance
“…These data could be useful for further MS-based analysis in order to enhance selectivity and sensitivity when more complex biological samples are analyzed. In this sense, sofosbuvir is typically analyzed in plasma using ESI in the positive ion mode [8] , [9] , [10] although the negative ionization mode also seems a potential alternative.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data could be useful for further MS-based analysis in order to enhance selectivity and sensitivity when more complex biological samples are analyzed. In this sense, sofosbuvir is typically analyzed in plasma using ESI in the positive ion mode [8] , [9] , [10] although the negative ionization mode also seems a potential alternative.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Liquid chromatography (LC) coupled to UV detection or mass spectrometry (MS) has been applied to determine oral anti-HCV drugs in pharmaceutical preparations [6] , biological samples [7] , [8] , [9] , [10] or even in wastewater [11] . In these studies, reversed phase (RP) liquid chromatography using silica-based C 18 columns is the most common mode.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of the SOF metabolite (GS‐331007) was similar in the presence and absence of DAC, while SOF exposures were ~35% higher in the presence of DAC (http://www.hcvdruginfo.ca/downloads/Hepatitis%20Cint_new%20NS5A%20inhibitors.pdf). The published methods for determination of SOF and/or DAC in human plasma are HPLC (Baker, El‐Kafrawy, Mahrous, & Belal, ; Hassib, Taha, Elkady, & Barakat, ; Nannetti et al, ; Srinivasu, Kumar, & Thirupathi, ), LC‐MS/MS (Abdallah, Abdel‐Megied, & Gouda, ; Ariaudo et al, ; Jiang et al, ; Nebsen & Elzanfaly, ; Qu, Wang, Zeng, Lub, & Yin, ; Rezk et al, , , b; Shi et al, ) and electrochemical detection (Azab & Fekry, ). To author's knowledge, this bio‐analytical method is the only LC‐MS/MS method for determination of SOF and DAC in human plasma with application to a pharmacokinetic study for both.…”
Section: Introductionmentioning
confidence: 99%
“…However, NS5A has no known enzymatic functions and so it is difficult to understand its mode of action (Belema et al, 2014;Smith, Regal, & Mohammad, 2016; Figure 1). There are eight metabolites of DAC, one of which (BMS-805215) has some activity; however, it is 100-fold less potent than the parent drug (Product monograph, 2016 (Baker, El-Kafrawy, Mahrous, & Belal, 2017;Hassib, Taha, Elkady, & Barakat, 2017;Nannetti et al, 2017;Srinivasu, Kumar, & Thirupathi, 2016), LC-MS/MS (Abdallah, Abdel-Megied, & Gouda, 2017;Ariaudo et al, 2016;Jiang et al, 2015;Nebsen & Elzanfaly, 2016;Qu, Wang, Zeng, Lub, & Yin, 2015;Rezk et al, 2015Shi et al, 2015) and electrochemical detection (Azab & Fekry, 2017…”
Section: Introductionmentioning
confidence: 99%
“…A literature review revealed a few methods have been reported for the quantitative determination of DAC and LED alone or in combination with other drugs. These include spectrophotometric, spectrofluorimetric, HPLC,, LC–MS/MS and electrochemical methods . The extensive use of the newly discovered antiviral drugs for the treatment of HCV necessitates the need to develop a cheap, rapid bio‐analytical method for their routine measurement in biological samples.…”
Section: Introductionmentioning
confidence: 99%